Creative suite-ening. - Baldwin, Roberto (Mac life)
Software comes and software goes, but some releases make every Mac user sits up and pay attention. Nothing commands the attention of designers, photographers, and anyone else with an artistic bent like the release of Adobe's nest Creative Suite. We've been putting the beta versions of CS5 through their paces for a couple of months now, and the results of our rigorous testing will be in your hands in next issue's reviews. To whet your appetite, our reviewers put together a list of the most interesting, useful, and impressive new features in Photoshop, Illustrator, Indesign, and Premiere. They also dove into what's new in the other key apps of CS5.